A new species of Atlantoscia Ferrara & Taiti, 1981 (Oniscidea: Philosciidae) from Rio Grande do Sul, Brazil - Campos-Filho,Ivanklin Soares (2012)
To date the genus Atlantoscia Ferrara and Taiti, 1981 includes two species, A. floridana (van Name, 1940) and A. rubromarginata Araujo and Leistikow, 1999. The species Atlantoscia petronioi sp.n. is described on the basis of material collected in a coastal dune forest area of the southern Rio Grande do Sul state, Brazil. This new species is characterized by antenna with accentuate setose sulcus from the peduncle to the distal article of the flagellum, outer endite of maxillula with slender seta among the outer group teeth and accessory tooth, one trifid tooth in the inner group, and male pleopod 1 endopod with distal part pointed and subapically not swollen.